Examining technology adoption trends in studio-based learning - Noor Hafizah; Mohd Zairul (Human Resource Management Academic Research Society, 2023)
In the context of studio-based learning, technology adoption has developed into a significant emergent technology in the fields of architecture, interior architecture, and landscape architecture. With the rapid advancement of technology, Industrial Revolution 4.0 is continuously evolving in unexpected ways in higher education. Studio-based learning, especially in architecture education, offers students access to various technology tools, enhancing their creativity and boosting interactive communication. However, the literature lacks studies about technology adoption in studio-based learning. Therefore, the aim of this study is to gather and review patterns and trends in the use of technology adoption in studio-based learning, from pre to post covid pandemic. This thematic review paper (TR) aims to synthesize literature from 2018-2023 on the technology adoption in studio-based learning using Atlas. ti 23. Thematic review (TR) from Scopus, Science Direct, IEEE, and Web of Science (WoS) had been employed, covering 134 peer-reviewed journal articles, which then had been analyzed in terms of Collaborative technologies with BIM, Digital Fabrication with CAD, and Integrated Metaverse. This thematic review offers an overview of the need for the personalization of digital technology in post-pandemic and future studio education. The findings and recommendations shall help future researchers in further exploring the use of technology in studio education, to cater to students’ personalization and needs of post-pandemics.